The acceptance of Tablet-PCs in classroom instruction: The teachers' perspectives - Ifenthaler, Dirk; Schweinbenz, V. (Elsevier, 2013)
Limited research has been conducted on the integration of Tablet-PCs in classroom instruction. This paper reports a qualitative study which investigates the acceptance of Tablet-PCs, seen as technological innovation, amongst teachers. The research approach intends to complement research on the acceptance of technology through a more detailed qualitative examination. Semi-structured interviews were conducted with 18 teachers during a pilot project introducing Tablet-PCs to classroom instruction at three different schools. The findings indicate diversity in the attitude of teachers towards the technology, but also with regards to the performance expectancy and the facilitating conditions. © 2012 Elsevier Ltd. All rights reserved.